Pengaruh Akuntabilitas, Transparansi Dan Partisipasi Masyarakat Terhadap Pengelolaan Dana Desa : Studi Kasus Di Desa Se-Kecamatan Abiansemal, Kabupaten Badung - Wati, Ni Putu Eka; Ayu, Putu Cita; Yuliantari, Ni Putu Yeni (UNHI Press, 2025)
community money is money used to support state administration. implementation of development, community development and community support. This research aims to determine the impact of accountability, transparency and community involvement on community financial governance in the Abiansemal region. All the local leaders in Abiansemal region,with a total of 271 people are the population used in this research. Total sample of 144 people using purposive sampling method. The tests carried out are instrument tests and classical assumption tests, Once the data reviewed using multiple processes checking options, t and f test. From this analysis, stating and answering those questions felt good. and community management in Abiansemal region. Transparency has a positive impact on community financial management in Abiansemal communities. Community involvement has a positive impact on community financial management in Abiansemal.